2010
DOI: 10.1021/jf903219u
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes and Dynamic Rheological Properties of Sarcoplasmic Proteins Subjected to pH-Shift Method

Abstract: Structural changes and dynamic rheological properties of sarcoplasmic proteins from striped catfish ( Pangasius hypophthalmus ) treated by various pH-shift processes were investigated. Isoelectric precipitation of acid-extracted sarcoplasmic proteins led to the lowest solubility in water. Sarcoplasmic proteins were unfolded after extremely acidic and alkaline extraction, exposing tryptophan and aliphatic residues. The alpha-helical structure was converted to beta-sheet following acidic extraction, whereas alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 38 publications
(73 reference statements)
0
42
0
Order By: Relevance
“…Sarcoplasmic proteins were extracted as described by Tadpitchayangkoon and others () with some modifications. Two grams (2 g) of fish mince was homogenized with 30 mL of cold deionized water for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Sarcoplasmic proteins were extracted as described by Tadpitchayangkoon and others () with some modifications. Two grams (2 g) of fish mince was homogenized with 30 mL of cold deionized water for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Water‐soluble protein was extracted according to the method of Tadpitchayangkoon et al . () with some modifications. Two grams of fish mince was homogenised with 30 mL cold deionised water using a homogeniser for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…Raghavan and Kristinsson () reported alkali‐treated myosin from catfish exhibited increased surface hydrophobicity compared with control samples. In addition, Tadpitchayangkoon, Park, Mayer, and Yongsawatdigul () observed gradual increases in surface hydrophobicity in soluble sarcoplasmic proteins isolated from striped catfish as pH increased from 6 to 12. Therefore, the present study suggested that blending a higher concentration of FPI compared with surimi can demonstrate increased surface hydrophobicity (Figure ).…”
Section: Resultsmentioning
confidence: 99%